Improvement in Sleep Architecture is associated with the Indication of Surgery in Syndromic Craniosynostosis - de Goederen, Robbin (Plast Reconstr Surg Glob Open, 2019)
Children with syndromic craniosynostosis (sCS) often suffer from obstructive sleep apnea (OSA) and intracranial hypertension (ICH). Both OSA and ICH might disrupt sleep architecture. However, it is unclear how surgically treating OSA or ICH affects sleep architecture. The aim of this study was twofold: to explore the usefulness of sleep architecture analysis in detecting disturbed sleep and to determine whether surgical treatment can improve it. METHODS: Eighty-three children with sCS and 35 control subjects, who had undergone a polysomnography (PSG), were included. Linear-mixed models showed the effects of OSA and ICH on sleep architecture parameters. In a subset of 19 patients, linear regression models illustrated the effects of OSA-indicated and ICH-indicated surgery on pre-to-postoperative changes. RESULTS: An increase in obstructive-apnea/hypopnea index (oAHI) was significantly associated with an increase in N2-sleep, arousal index, and respiratory-arousal index and a decrease in REM-sleep, N3-sleep, sleep efficiency, and sleep quality. ICH and having sCS were not related to any change in sleep architecture. OSA-indicated surgery significantly increased the total sleep time and sleep efficiency and decreased the arousal index and respiratory-arousal index. ICH-indicated surgery significantly decreased REM-sleep, N1-sleep, sleep efficiency, and sleep quality. CONCLUSIONS: For routine detection of disturbed sleep in individual subjects, PSG-assessed sleep architecture is currently not useful. OSA does disrupt sleep architecture, but ICH does not. OSA-indicated surgery improves sleep architecture, which stresses the importance of treating OSA to assure adequate sleep. ICH-indicated surgery affects sleep architecture, although it is not clear whether this is a positive or negative effect.